Papel do fator de inibição de migração de macrófagos (MIF) na infecção por Plasmodium berghei NK65GFP durante a gestação em camundongos C57BL/6 - Duran-Rodriguez, Andrea Tatiana (2022)
Malaria in pregnancy can lead to maternal death, miscarriage and low birth weight. Macrophage migration inhibitory factor (MIF) is a pluripotent cytokine that has an important role in normal pregnancy and delivery, and its level have been shown to increase in the placenta of pregnant women with malaria. To evaluate the role of MIF in experimental gestational malaria, C57BL/6 and MIF-/- mice were inoculated or not with Plasmodium berghei (Pb) NK65GFP at three gestational stages. Maternal and embryonic/fetal parameters associated with adverse pregnancy outcomes were evaluated, as well as the numbers of mast cells, uterine natural killer cells (uNK), CD11b+ cells and MCP1+ cells. In addition, the expression in the uterus/placenta of molecules important for the maintenance of pregnancy or involved in the immune response and MIF signaling, such as MIF, DdT, iNOS, ARG1, VEGF and Tim3, were evaluated. In early pregnancy, mice expressing MIF had more adverse pregnancy outcomes as a consequence of infection, such as decreased decidua area and lower ratio between uterine horn weight and number of implantation sites per animal. Additionally, it was demonstrated that infected C57BL/6 mice showed a decrease in uNK cells and an increase in CD11b+ cells in the decidua. In contrast, uninfected MIF-/- mice had lower counts of these cells, which were not altered in response to Pb infection. MCP1+ cells were also increased in C57BL/6 infected animals in comparison with MIF-/- infected group and the uninfected C57BL/6 group. C57BL/6 animals with 8 days of gestation (DG) infected showed lower levels of expression of ARG and VEGF, compared to the MIF-/- group after infection. In mid-gestational period, inadequate remodeling of spiral arteries and decreased placental vascular space were observed in C57BL/6 infected animals, but not in MIF-/- infected mice, in which uNK cells decreased but increased VEGF mRNA expression. Furthermore, in the implantation sites of MIF-/- animals, higher numbers of CD11b+ cells were observed, accompanied by a higher expression of ARG1 and lower expression of iNOS, indicating that the better pregnancy outcomes presented in the absence of MIF could be associated with a predominance of macrophages with an anti-inflammatory profile at the maternal-fetal interface during infection in this gestational period. Late in pregnancy, MIF deficiency led to higher levels of parasitemia as well as increased hemozoin deposits in the spleen and placental labyrinth. Fetuses from infected animals were underweight regardless of the presence or absence of MIF, although this effect was more pronounced in fetuses from MIF-/- infected mothers. MIF seems to contribute to the deleterious effects of gestational malaria in the initial and middle thirds of pregnancy and to participate in the control of maternal parasitemia and tissue hemozoin deposition at the end of pregnancy, reflecting fetal weight restriction.